Evaluation of the Quality of Coastal Ecosystems in the Spermonde Archipelago Using Macroalgae as Indicators - Rispah Hamzah; Luchman Hakim; Catur Retnaningdyah (Journal of Tropical Life Science, 2020)
The quality of water in Spermonde Archipelago, South Sulawesi has decreased as a result of high human activities and land use, this can have an impact on the life of marine biota. Macroalgae is suitable for bioindicators because they live in a sessile manner, can accumulate metals and distributed widely. This research aimed to determine coastal ecosystem quality by using macroalgae as indicators on five islands that had different anthropogenic stresses. The research was carried out in April 2019 on Barrang Caddi, Bonebatang, Barrang Lompo, Kodingareng Keke, and Badi Islands. Community structures observed included taxa richness, diversity, evenness, dominance of macroalgae and physicochemical parameters (temperature, turbidity, pH, salinity, DO, BOD, H2S, oil, grease, total Phosphate, and nitrate) as well as the measurement of the ecological condition using Quality of Rocky Bottoms (CFR) index. The results showed that physicochemical parameters (temperature, turbidity, pH, salinity, DO, H2S, oil, grease, total Phosphate) of the water still met the quality standards of sea water based on Decree of the State Minister for Environment No. 51/2004 for marine biota and other standards for macroalgae growth. BOD and nitrate have exceeded sea water quality standards for marine biota (20 mg/L for BOD and 0.008 mg/L for nitrates). A total of nine species of macroalgae were found in Barrang Caddi and Badi Island, three species in Bonebatang, and five species in Kodingareng Keke and Barrang Lompo Island. The result of Principal Component Analysis (PCA) and Biplot showed that physicochemical water quality has an influence on the macroalgae community structure. While the CFR index shows Barrang Caddi and Badi Island have poor ecological conditions and Bonebatang, Barrang Lompo, and Kodingareng Keke have bad ecological condition.